(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article introduces the notion of supply chain, which is founded on two dimensions: the basic processes of a supply chain, and the concept of corporate social responsibility, which are both discussed in detail. It is proposed that a responsible supply chain is achieved through the manifestation of fundamental values by supply chain participants, as well as through their plans and tactics. A further discussion is included in this paper regarding the individual supply chain actors’ responsibility for assuring that a responsible supply chain exists that is outside of their direct control. A conceptual model as well as a definition of a responsible supply chain are provided. We have developed a model that not only gives structure to the existing studies, but also produces new constructs and linkages that help to expand our understanding of the responsible supply chain. The work is based on an evaluation of research articles that were published between since years ago and contained parts of corporate social responsibility and supply chain procedures